2012
DOI: 10.1109/tie.2011.2141097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Asynchronously Controlled Electrostatic Energy Harvesters

Abstract: Mechanical to electrical energy conversion employing variable capacitors is assisted by electronic circuits that can have synchronous or asynchronous architectures. The later does not require synchronization of electrical events with mechanical motion, which eliminates difficulties in gate clocking and the power consumption associated with intelligent control circuitry. However, implementation of asynchronous energy harvesting circuits with the mechanical-to-electrical converter can be detrimental to the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Kempitiya et al [34] presented an electrostatic generator with asynchronous control and charge flyback mechanism to optimise the useful energy generated by the harvester. The authors' theoretical and experimental investigations showed that there is an optimum value for the storage capacitor and the cycle number for maximum scavenging of ambient energy.…”
Section: B Switched Constant Charge Systemsmentioning
confidence: 99%
“…Kempitiya et al [34] presented an electrostatic generator with asynchronous control and charge flyback mechanism to optimise the useful energy generated by the harvester. The authors' theoretical and experimental investigations showed that there is an optimum value for the storage capacitor and the cycle number for maximum scavenging of ambient energy.…”
Section: B Switched Constant Charge Systemsmentioning
confidence: 99%
“…In either case, the robustness of the completed device is compromised due to high strain on the suspension system and should be compensated for by adding in-plane and out-of-plane stoppers to the device and package design. For in-plane devices, having a thick device layer has been shown to be optimal in terms of energy gain per harvesting cycle [12][13]. The tradeoff is that thick device layers limit the width of capacitive gaps created by DRIE due to aspect ratio limitations.…”
Section: Harvestersmentioning
confidence: 99%
“…System modeling also shows that the maximum power is extracted when the system approaches synchronous operation. However, there is a region of interest where the storage capacitor can be optimized to produce almost 70% of the ideal power taken as the power harvested with synchronous converters when neglecting the power consumption associated with synchronizing control circuitry [13].…”
Section: Power Mangement Control Circuitsmentioning
confidence: 99%
“…In the second phase, the charges at higher potential are transferred to a load. Finally, the distance of the plates decreases and the capacitance returns to its initial value, ready for a new cycle [3], [6].…”
Section: Introductionmentioning
confidence: 99%